Overcoming the challenges of ai adoption in banking sector: Security, regulation, and infrastructure - Novi Handayani Simbolon; Fatma Dwi Jati; Sondang Beatrix Siahaan (International Journal of Applied Finance and Business Studies, 2025)
The adoption of Artificial Intelligence (AI) in the banking sector has rapidly expanded, because bringing benefits in areas such as risk assesment, fraud detection, and personalized services. However, AI adoption faces significant challenges related to security, regulation, and infrastructure. While previous research has explored AI’s potential, there is a gap in comprehensive studies addresing these core challenges, particularly in emerging markets. This research aims to identify and analyze the main barriers to AI adoption in banking, focusing on security, regulatory issues, and infraastructure readiness. A systematic literature review was conducted, synthesizing findings from academic articles, banking reports, and regulatory guidelines published between 2020 and 2024. The result reveal that concerns over data security, inconsistent regulations, and insuffiecient infrastructure hinder AI’s full potential. The concludes of this research showed banks must prioritize cybersecurity, advocate for clearer regulations, and invest in digital infrastrcuture to ensure the secure AI adoption in banking activities.